Determinan Pemanfaatan Posbindu Penyakit Tidak Menular oleh Masyarakat di RW 36 Padukuhan Ngabean Kulon Sinduharjo Ngaglik Sleman - Reza Nur Fatimah; Wulandari, Dewi Ariyani; Damayanti, Susi (Jurnal Kesehatan Komunitas, 2023)
Non-communicable disease is a chronic disease that is very dangerous because it does not give symptoms or complaints. Minimum service standards for screening NCD at Ngaglik I Public Health have not reached the target due to the low utilization of PTM Posbindu. This study aims to analyze the determinants of the use of NCD Posbindu by the community at the hamlet of Ngabean Kulon 36 Sinduharjo Ngaglik Sleman. This research was conducted at Ngudi Waras Posbindu, hamlet of Ngabean Kulon 36 Sinduharjo Ngaglik Sleman. This type of research used quantitative methods with a cross-sectional approach. The sample was taken by proportional random sampling method with a total sample of 88 respondents. The data analysis used bivariate analysis with Fisher’s test and multivariate analysis with logistic regression. The results of the bivariate analysis showed knowledge (p=0.000), motivation (p=0.000), perceived benefits (p=0.000), health facilities (p=0.000), family support (p=0.000), and cadre support (p=0.020). Factors influencing Posbindu PTM utilization were health facilities (p=0.004) and family support (p=0.029). The most dominant factor in the utilization of Posbindu PTM is health facilities (p=0.004) with OR = 60.079, which means that health facilities have 60.079 opportunities to influence the community in utilizing Posbindu PTM. The need to assist cadres, increase existing resources to complement lacking health facilities, and innovate activities to attract people to take advantage of Posbindu for non-communicable diseases.